(3COH GdcGJHs - (3YHO Gddg Hf eSde Hf bJjHI GdOjnfnhQqj, CHh eMeO, GHf obnJrjnHI, J (B276 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg HLejY eMGeOg hGdKfGA Ydjg HeG gh Cgdg, hGdUdGI hGdSdGe Ydi QShdg GdeUWai hBdg aEfj QCjJ CcKQ Cgd ReGffG Yf SHjd GdCOH fGcHjf s
(3BNQgG (B:s
(3hEfeG LF HgPG GdeUOQ eNGdaI ddCaYGd, dCf GdCaYGd hEf ENJdaJ CHfjJgG hGMOI aj GdeYfi Ef TGA Gddg Je GdSaQ GdKGfj ef COH GdcGJH HMeO Gddg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B137s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B13 s
Keywords: (3GdCOHs